Antibiotic resistance profiles and mutations that might affect drug susceptibility in metagenome-assembled genomes of Legionella pneumophila and Aeromonas species from municipal wastewater - Evida Poopedi; Rian Pierneef; Tanusha Singh; Annancietar Gomba (BMC Microbiology)
Abstract Antibiotic resistance (AR) has emerged as a significant global health issue. Wastewater treatment plants (WWTPs) contain diverse bacterial communities, including pathogens, and have been identified as crucial reservoirs for the emergence and dissemination of AR. The present study aimed to identify antibiotic resistance genes (ARGs) and screen for the presence of mutations associated with AR in Legionella pneumophila and Aeromonas spp. from municipal wastewater. Metagenome-assembled genomes (MAGs) of L. pneumophila and Aeromonas spp. were reconstructed to investigate the molecular mechanisms of AR in these organisms. A total of 138 nonsynonymous single nucleotide variants (SNVs) in seven genes associated with AR and one deletion mutation in the lpeB gene were identified in L. pneumophila. In Aeromonas spp., two (aph(6)-Id and aph(3’’)-Ib) and five (bla MOX−4, bla OXA−1143, bla OXA−724, cepH, and imiH) ARGs conferring resistance to aminoglycosides and β-lactams were identified, respectively. Moreover, this study presents β-lactam resistance genes, bla OXA−1143 and bla OXA−724, for the first time in Aeromonas spp. from a municipal WWTP. In conclusion, these findings shed light on the molecular mechanisms through which clinically relevant pathogenic bacteria such as L. pneumophila and Aeromonas spp. found in natural environments like municipal wastewater acquire AR.